Institutionalizing Countercyclical Investment : A Framework for Long-term Asset Owners - Jones, Bradley (IMF Working Papers; Working Paper, 2016)
Do portfolio shifts by the world's largest asset owners respond procyclically to past returns, or countercyclically to valuations? And if countercyclical investment (with both market-stabilizing and return-generating properties) is a public and private good, how might asset owners be empowered to do more of it? These two questions motivate this study. Based on analysis of representative portfolios (totaling USD 24 trillion) for a range of asset owners (central banks, pension funds, insurers and endowments), portfolio changes typically appear procyclical. In response, I suggest a framework aimed at jointly bolstering long-term returns and financial stability should: (i) embed governance practices to mitigate 'multi-year return chasing;' (ii) rebalance to benchmarks with factor exposures best suited to long-term investors; (iii) minimize principal-agent frictions; (iv) calibrate risk management to minimize long-term shortfall risk (not short-term price volatility); and (v) ensure regulatory conventions do not amplify procyclicality at the worst possible times.